Chemoresistance factors in non-small cell lung cancer - А. I. Shevchenko; А. P. Коlesnik; А. V. Каdzhoian; V. А. Кuzmenko (Patologìâ)
Lung cancer takes the leading position in cancer morbidity and mortality structure in the world and Ukraine. Advanced stages are diagnosed in more than 70% of lung cancer patients. Chemotherapy remains the main method of treatment for advanced lung cancer. Currently, the standard of chemotherapy in patients with III–IV stages of non-small cell lung cancer (NSCLC) is a combination of cisplatin/carboplatin with paclitaxel, etoposide, gemcitabine and vinorelbine. Although, the objective response rate after chemotherapy treatment is only about 20–50%. Low rates of chemotherapy efficacy are connected with chemoresistance of tumor to definite chemotherapeutic agents. Tumor chemoresistance is the result of different tumor intracellular mechanisms activity. Basing on current data we tried to analyze prognostic and predictive value of main chemoresistance factors in NSCLC.